Intraindividual comparison of preoperative 99mTc-MDP SPECT/CT and intraoperative and histopathological findings in patients with bisphosphonate- or denosumab-related osteonecrosis of the jaw. Issue 8 (October 2015) - Assaf, Alexandre T.; Zrnc, Tomislav A.; Remus, Chressen C.; Adam, Gerhard; Zustin, Jozef; Heiland, Max; Friedrich, Reinhard E.; Derlin, Thorsten
Abstract: Purpose: Bisphosphonate- or denosumab-related osteonecrosis of the jaw (BRONJ/DRONJ) requires reliable preoperative assessment of the extent of disease for surgical planning. The aim of this study was to compare the extent of BRONJ/DRONJ as detected by Tc-99m-methylene diphosphonate (MDP) bone scintigraphy with intraoperative and histopathological findings, and to assess the additional value of hybrid single photon emission computed tomography/computed tomography (SPECT/CT) for evaluation of disease. Material and methods: Twenty-one patients with BRONJ/DRONJ underwent three-phase bone scintigraphy including SPECT/CT. The diagnostic certainty using conventional SPECT or fused SPECT/CT imaging was compared. Location and extent of disease on scintigraphic imaging and pre- and intra-operative clinical assessment were compared. Intraoperative and histopathological findings served as reference standard. Results: A total of 29 sites of BRONJ/DRONJ were histopathologically confirmed in 21 patients. Bone scintigraphy demonstrated increased perfusion in 57.1% of patients, increased blood pool in 76.2%, and increased tracer accumulation at the metabolic phase in all patients. The intensity of tracer accumulation at the metabolic phase correlated significantly with clinical stage of disease ( r s  = 0.47, p  = 0.03). Clinical examination ( p  < 0.0001), but not SPECT ( p  = 0.19), underestimated the extent of disease as determined by surgical evaluation. SPECT/CT offered a significantly higher diagnostic certainty ( p <  0.0001). Conclusion: In patients with BRONJ/DRONJ, the true extent of osseous lesions as determined by surgery is significantly underestimated by clinical examination. Tc-99m-MDP bone scintigraphy can reliably predict the extent of disease. Hybrid SPECT/CT may significantly increase the diagnostic certainty of anatomical localization.